Star trek III : the search for Spock [videorecording (Blu-Ray)] - Roddenberry, Gene; Shatner, William; Nimoy, Leonard; Kelley, DeForest, 1920-1999; Doohan, James; Takei, George, 1937-; Koenig, Walter, 1936-; Nichols, Nichelle (Paramount, 2009)
In the wake of Spock's ultimate act of sacrifice, the crew of the U.S.S. Enterprise returns to Earth from the newly formed Genesis planet. Upon arrival, the crew learns that life back home will not be easier: Scotty gets reassigned, "Bones" appears to be going insane, and the Enterprise is to be decommissioned.